Oral Motor Disorders and Speech Disorders as Risk Factors for Difficulty Eating in Children Aged 6-60 Months. - Audi Yudhasmara; Asrini Kaninta Adani; Ida Narulita Dewi; Widodo Judarwanto; Sandiaz Yudhasmara (Journal Of Social Science (JoSS), 2024)
Picky eating is not a diagnosis or disease, but rather an indication or a symptom of underlying irregularities within a child's physiology. It manifests as a refusal to consume food or drink or struggles with ingesting appropriate types and quantities for their age, from the simple act of opening one's mouth without coercion, to chewing, swallowing, and digesting without any external pressure or need for specific nutrients or medications. Numerous risk factors have been identified as significant contributors to the presence of picky eating in children, most notably oral motor disorders and delayed speech development. This observational analytic study involved 138 children between the ages of 6-60 months as subjects, with interviews conducted by their parents serving as the primary method of data collection. Developmental Pre-screening Questionnaire (KPSP) and modified questionnaire of risk factor of picky eating were utilized to evaluate each child's overall development and assess potential risk factors related to feeding difficulties. Findings from this investigation indicated that both oral motor disorders and delayed speech had notable effects on children aged 6-60 months residing in MaIang.